Peripapillary fluorescence lifetime reveals age-dependent changes using fluorescence lifetime imaging ophthalmoscopy in rats. (November 2018) - Teister, J.; Liu, A.; Wolters, D.; Pfeiffer, N.; Grus, F.H.
Abstract: Many fundus diseases accompany fundus autofluorescence change. Fluorescence lifetime imaging ophthalmoscope (FLIO) is a latest technique in imaging fundus autofluorescence. With FLIO, the fundus fluorescence lifetime (FLT) is recorded topographically, assisting to diagnose and monitor multiple fundus diseases. The purpose of this study was to evaluate the repeatability of FLT using FLIO on adult rats and to analyze the age-dependency of the peripapillary FLT of the fundus in a short spectral channel (498–560 nm) and a long spectral channel (560–720 nm). Sprague Dawley rats (n of eyes = 10) were used for repeatability experiments. Age-dependent changes were investigated in young (two months old, n of eyes = 20) and old (eight months old, n of eyes = 10) rats. Repeatability experiments showed highly corresponding data for all segments in both spectral channel, with higher repeatability in the short spectral channel. FLT decreased significantly in all areas in the short (young: 991 ± 29 ps; old: 547 ± 42 ps) and long (young: 382 ± 28 ps; old: 261 ± 16 ps) spectral channels, indicating an overall metabolic change of the fundus in old animals. FLT of veins increased in the short spectral channel (young: 385 ± 43 ps; old: 424 ± 25 ps) and no change was observed in the long spectral channel (young: 274 ± 9 ps; old: 269 ± 24 ps). FLIO represents a highly repeatable and sensitive method to detect changes of the FLT in aged eyes for monitoring the degeneration of the rodent retinae. Highlights: FLIO is highly repeatable in the short spectral channel. Rodent fundus fluorescence lifetime is sensitive to aging. FLIO can be used as a imaging tool for monitoring the fundus.